Image challenge: A complex PUO. (October 2020) - Dunn, C.; Wong, N.; Griffin, Y.; White, H.; Wiselka, M.J.
Abstract: A 67-year-old Caucasian woman was admitted with a four week history of neck and arm pain, weight loss, abdominal bloating, anorexia and pyrexia. Initial investigations failed to find a cause for her on-going ill health and pyrexia. A CT-PET scan was performed. Highlights: 67-year old Caucasian lady PUO for 4 weeks Whole body 18F-FDG PET-CT (PET-CT) scan Giant cell/Takayasu arteritis